Role of Job Stress on Working of College Teachers in Chandigarh: An Empirical Study: Impact of Job Stress on College Teachers' Performance in Chandigarh (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The main purpose of this study is to show the effect of different variables of job stress on working of college teachers in Chandigarh. Data for this study was collected from 102 teachers working in different colleges of Chandigarh with the help of a well designed questionnaire and was analyzed with the help of multiple linear regressions. The results from the analysis show that some variables are impacting working positively whereas some are not.